China : Macroeconomic Cycles in the 1980's - Khor, Hoe. (Washington, D.C. : International Monetary Fund, 1991)
This paper explores the links between reforms, macroeconomic management and the occurrence of macroeconomic instability in China during the last decade, drawing upon previous analytical work and also employing the 'Granger causality' test. It is concluded that the cycles did not originate with the reforms; rather their characteristics were modified by structural changes in the economy. It is further argued that the incompleteness of reforms (which renders macroeconomic management difficult) had the effect of exacerbating the cycles by increasing their amplitude and frequency. Finally, results from the Granger tests suggest that broad money would be a good intermediate target for monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet